Promoting brainstorming technique in teaching writing - Fandini, Pramesti Wahyu; Khoiriyah, Khoiriyah; Aji, Mahendra Puji Permana (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2023)
Writing is one of skills to express ideas, feelings, and thoughts in the form of words to create sentences by paying attention to several punctuation. Brainstorming technique plays a significant part not only in the writing process of idea generation but also in fostering students' creativity, especially in producing descriptive texts. The purpose of this study is to determine the effect of brainstorming techniques on the students’ writing skill of the tenth grade at SMA Negeri 7 Kediri. The method used in this study was quantitative method with pre-experimental design by using pretest and post-test. The population of this study was the tenth grade students of SMA Negeri 7 Kediri and the sample was taken from class X- ECP 2 consisting of 32 students. The technique of collecting data used was pretest, treatment, post-test and it will be analyzed by using t-test through SPSS version 23. The results of this present study showed that Brainstorming technique had significant impact on the students’ writing skill of the tenth grade at SMAN 7 Kediri. It can be seen that pretest was higher than post-test with the mean value of pretest was 61.47 and the mean value of post-test was 83.06. The standard deviation of pretest was 13.320 while standard deviation of post-test was 6.101. Finally, this research will be useful in the teaching writing. The research can be useful to the teachers, students and the readers.